Beyond the Interface: Usability and Value Creation in the Public Services Ecosystem - Figueiredo, Rejane M. da C.; Judice, Andrea C. B.; Judice, Marcelo O.; Pedrosa, Glauco V.; Costa, Flavio F.; Gardenghi, John L. C.; Ferreira, Stefani P.; Guedes, Bruna de O. (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2025: Anais do XXIV Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2025)
Introduction: Digital transformation in the Brazilian public sector demands user-centered digital services that are accessible, effcient, and able to create public value. Objective: This report analyzes the usability of SplitGov system, a federal platform for contract and cost-sharing management, using the Public Service Ecosystem (PSE) model. Methodology: A triangulated evaluation combined heuristic analysis, guided navigation, and usability testing with public servants, aligned with UX principles and digital government strategies. Results: The study identifed barriers related to accessibility, interface consistency, and task fow, proposing redesign recommendations to improve navigation, information retrieval, and user alignment.